Pengaruh Profitabilitas, Likuiditas, dan Pertumbuhan Perusahaan Terhadap Struktur Modal: Studi pada Perusahaan Food and Beverage yang Go Public di Bursa Efek Indonesia Periode 2020 – 2023 - Theresita Angela Zita Dewi; Usep Syaipudin (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
An optimal capital structure is a crucial factor in maintaining financial stability and supporting business growth, particularly in the dynamic food and beverage sector. This study aims to analyze the influence of profitability, liquidity, and company growth on the capital structure of food and beverage companies listed on the Indonesia Stock Exchange during the period 2020–2023. This quantitative research uses secondary data obtained from the Indonesia Capital Market Directory. The sample consists of 71 companies selected using purposive sampling. Data were analyzed using multiple linear regression, supported by classical assumption tests to ensure the validity of the results. The findings reveal that profitability has a negative but insignificant impact on capital structure, while liquidity and company growth have significant negative impacts. These results indicate that higher profitability, liquidity, and growth tend to reduce the reliance on external financing. The implications of this study provide insights for companies in formulating effective financing strategies and offer important considerations for investors in evaluating the risks and investment opportunities in this sector.